The Application of Skill Play Stimulation to Train Gross Motor Skills in Children with Autism at Sinar Indonesia School, Cibubur - Aprillia, Mia; Choiriyah; Lily Yuntina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Gross motor development in early childhood is a fundamental aspect in supporting physical, social, and cognitive growth. Children with autism often experience difficulties in gross motor skills such as walking, kicking, and throwing, thus requiring structured learning strategies. This study aims to analyze the application of skill play stimulation in training gross motor skills in children with autism at Sinar Indonesia School Cibubur. This study used a descriptive qualitative approach with a case study design. The research population consisted of all children with autism who participated in the inclusion program, while the sample was selected purposively, namely one child with gross motor delays. The research instruments included participatory observation, semi-structured interviews with the principal, classroom teachers, and assistant teachers, as well as photo and video documentation. Data analysis was conducted using Miles and Huberman's interactive model, which included data reduction, data presentation, and conclusion drawing. The results showed that the application of skill play involving kicking a ball, walking on a balance beam, and throwing and catching a ball was able to improve the children's coordination, balance, concentration, and self-confidence. The support of assistant teachers, the use of simple instructions and visual media, and the giving of praise and rewards were important factors in the success of the stimulation. These findings confirm that skill play is effective in inclusive learning to improve the gross motor development of children with autism. Further research is recommended to involve more participants and extend the duration of the intervention to strengthen the generalization of the results.